HEADACHES AND OBSTRUCTIVE SLEEP APNEA - OUAMMOU Imane (Faculté de Médecine et de Pharmacie, Rabat - Thèse de médecine, 2022)
Obstructive sleep apnea (OSA) is a common disorder characterized by partial or complete obstruction of the upper airways during sleep causing repeated airflow cessation or a significant decrease in airflow in the presence of breathing effort (hypopnea and/or apnea), oxygen desaturation, and sleep disruption. Headaches are frequently reported by patients suffering from OSA and sleep apnea headache is already defined and classified by the international headache society in the ICHD-3. However, and due to the wide range of OSA symptoms, headaches are rarely investigated as a common symptom of obstructive sleep apnea to identify this common sleep disorder that goes frequently undiagnosed. This is a retrospective, descriptive and analytical study conducted by the neurophysiology department of Mohammed V Teaching Military Hospital in Rabat. 34 patients with confirmed OSA were included and recruited into the study within a period of 24 months (2020-2021). 15 patients had OSA without headache (group A) and 19 patients had OSA associated with headache (group B). The prevalence of headaches in OSA patients was 51,8% in our study and our statistics have not objectified a relationship between OSA and headaches. We found a gender difference between the two groups with a female predominance in the entire sample (52,9% of females in all patients) but only significant in group B (78,9 % of females in group B) (p<0,01). The age, BMI, and AHI were similar between the two groups. 70,6% of patients had nocturia in the entire sample and depression was seen in group B only (p=0,053). 94,1% of patients received CPAP therapy, and 2,9% received oral appliance therapy (MAD). According to our study, OSA seems more frequent in women and is usually associated with depression. Most patients reported a morning headache that occurs more than 15 days per month with no associated symptoms; as well as moderate pain and a band-like location. The small size sample might have influenced the findings as it was the main limitation of this work. A study on a larger sample is required to confirm our findings. In our population, both OSA and headache are common health problems, early diagnosis and treatment can reduce both medical and societal consequences, as well as their costs.
Keywords: Obstructive sleep apnea; headaches; continuous positive airway pressure; oral appliance therapy (MAD); Obstructive sleep apnea; Headaches; Continuous positive airway pressure; Oral appliance therapy (MAD .